Isogeometric analysis with trimming technique for quadruple arch‐cut ridged circle waveguide. (14th July 2016) - Li, Peng; Liu, Jun; Lin, Gao; Lu, Shan; Zhang, Pengchong
Abstract: The conventional non‐uniform rational B‐spline (NURBS)‐based isogeometric analysis (IGA) preserves the exact description of geometrical shapes and significantly improves the computational accuracy, but suffers from the topological limitations of a single intact NURBS patch in the parameter space, which renders IGA to be applied in complex topology like the ridged structure inconvenient. In this present work, trimming technique which is the isogeometric approach for handling two‐dimensional topologically complicated geometry with a single patch is employed to demonstrate how this issue can be resolved, and further extended to analyze the quadruple arch‐cut ridged circular waveguide. The main benefit of the proposed approach is that only one patch is sufficient to represent the complex two‐dimensional topology such as circular or any degrees of polygonal shapes. Because the finite element constituents of the trimmed elements are calculated and mapped into underlying global control variables by remodeling the trimmed elements as a single patch, various properties of conventional IGA are maintained. Numerical example illustrates the flexibility for describing complicated two‐dimensional domain, and high computational accuracy and efficiency of present method with much less degree of freedom compared to commercial finite‐element software package. Effects of arch‐cut ridge dimensions on the cut‐off wave numbers of modes are investigated in details. Copyright © 2016 John Wiley & Sons, Ltd.